DEVELOPMENT OF AN INNOVATIVE TECHNOLOGY FOR WORKING WITH STUDENTS WITH LOW ACADEMIC PERFORMANCE. (IN THE EXAMPLE OF 5-6 GRADES) - Ravshanbek Islamov Turgunalievich (International Scientific and Current Research Conferences, 2023)
This research work is devoted to the development of an innovative technology aimed at improving the performance of students in grades 5-6 with a low level of education. In modern educational conditions, an urgent problem is the individualization of education and support for schoolchildren who experience difficulties in mastering educational material. The study is based on the application of modern pedagogical and psychological-pedagogical methods, as well as the use of information and communication technologies. The main goal of this technology is to create an individualized educational environment that contributes to the educational progress of students with poor academic performance.